2000
DOI: 10.1002/(sici)1521-379x(200001)52:1<18::aid-star18>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Nitrogen Sources on Raw Starch-Digesting Glucoamylase Production of Rhizopus sp. MKU 40

Abstract: In a liquid cultivation of Rhizopus sp. MKU 40, supplementation of the medium with 1.5% (w/v) organic nitrogen sources (neopeptone, casein from milk, and meat extract) had a slightly positive effect on glucoamylase (GA) (EC 3.2.1.3) activity compared with the medium lacking organic nitrogen sources. The addition of organic nitrogen sources induced production of protease. Supplementation of the medium with 1.5% (w/v) organic nitrogen sources resulted in an acid and neutral protease activity of 11 — 25 U/mL and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…[19], Rhizopus sp. [20], and Cryptococcus sp. [21], are good producers of raw starch-digesting amylases, capable of acting at low pH and high temperatures, while there are small number of reports on raw starch degradation by ␣-amylases purified from Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…[19], Rhizopus sp. [20], and Cryptococcus sp. [21], are good producers of raw starch-digesting amylases, capable of acting at low pH and high temperatures, while there are small number of reports on raw starch degradation by ␣-amylases purified from Bacillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Potato peel waste as a solid substrate also performs the role of the physical structure that supports the growth of microorganisms in addition to the rich nutrients supply (Gebrechristos and Chen, 2018). Glucohydrolase production in SSF has been reported by Morita and Fujio, 2000;Wang et al, 2006;Sun and Zhang, 2007;Zambare, 2011, andOnofre et al, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…The results shown that glucohydrolase activity increases with increase in moisture content from 40% to 50%, was observed maximum at 50% and then gradually fall off at 60% moisture content as the substrate became waterlogged and decrease surface to volume ratio (Figure 8). Morita and Fujio, (2000) reported that 45% initial moisture level was optimum for enzyme production by Rhizopus sp. MKU 40.…”
Section: Influence Of Moisture Level On Glucohydrolase Productionmentioning
confidence: 99%
“…Recently, global business has concentrated on raw starchdigesting amylases capable of acting at low pH and high temperatures, which could be valuable in terms of efficiently simplifying the process of starch conversion. Microbial amylases have successfully replaced the chemical hydrolysis of starch in industries 10 .…”
Section: Introductionmentioning
confidence: 99%